2006
DOI: 10.1007/s00198-006-0131-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of axial and femoral bone mineral density and parameters of mandibular bone quality in patients receiving dental implants

Abstract: We conclude that there is no association between systemic osteoporosis (axial and femur) and parameters of poor mandibular bone quality. The loss of one implant (1.2%) is compatible with the literature and cannot be attributed to systemic osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Concerns have therefore been raised about the interrelationship between endosseous implant and osteoporosis, a condition associated with a decrease in bone quality and quantity . Although there is still no common consensus about the influence of osteoporosis on implant osseointegration, studies in patients seem to indicate that osteoporosis is not an absolute contraindication for dental implant; osseointegration in osteoporotic bone can be obtained although may be delayed …”
Section: Introductionmentioning
confidence: 99%
“…Concerns have therefore been raised about the interrelationship between endosseous implant and osteoporosis, a condition associated with a decrease in bone quality and quantity . Although there is still no common consensus about the influence of osteoporosis on implant osseointegration, studies in patients seem to indicate that osteoporosis is not an absolute contraindication for dental implant; osseointegration in osteoporotic bone can be obtained although may be delayed …”
Section: Introductionmentioning
confidence: 99%
“…The histomorphometric results were also not different either between the groups once the osseointegration was established. 2 In aAnother retrospective study with a follow-up to of 3 years and 4 months for assessed 70 implants placed in patients diagnosed with osteoporosis at the lumbar level of the spine and hip., there This study showedreported was a success rate of 97% for the maxilla and 97.3% The rReduction of both bone density and of mineral content of in peripheral bones has been associated with high resorption and atrophy of edentulous jaws, but although no relationship was found has been established with greater increased loss of implants.…”
Section: Disscusiondiscussionmentioning
confidence: 99%
“…Other authors have also shown that systemic osteoporosis was not considered an important indicator of dental implant outcome under masticatory function [21, 36, 37]. …”
Section: Discussionmentioning
confidence: 99%